2014
DOI: 10.1038/modpathol.2013.158
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence confocal microscopy for pathologists

Abstract: Confocal microscopy is a non-invasive method of optical imaging that may provide microscopic images of untreated tissue that correspond almost perfectly to hematoxylin- and eosin-stained slides. Nowadays, following two confocal imaging systems are available: (1) reflectance confocal microscopy, based on the natural differences in refractive indices of subcellular structures within the tissues; (2) fluorescence confocal microscopy, based on the use of fluorochromes, such as acridine orange, to increase the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 28 publications
(31 reference statements)
3
76
0
4
Order By: Relevance
“…For meningiomas, some diagnostic criteria such as typical meningothelial, fibroblastic or transitional architecture were identifiable. The features of brain metastasis on confocal microscopy are the same encountered on formalin-fixed tissue section: cohesive or discohesive large and pleomorphic cells [9]. Our work provides additional data showing that ex vivo confocal microscopy is capable of identifying diagnostic histopathologic hallmarks of brain tumors and for some of them histopathological subtype.…”
Section: Discussionmentioning
confidence: 65%
“…For meningiomas, some diagnostic criteria such as typical meningothelial, fibroblastic or transitional architecture were identifiable. The features of brain metastasis on confocal microscopy are the same encountered on formalin-fixed tissue section: cohesive or discohesive large and pleomorphic cells [9]. Our work provides additional data showing that ex vivo confocal microscopy is capable of identifying diagnostic histopathologic hallmarks of brain tumors and for some of them histopathological subtype.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies using bench-top confocal reflectance [42] and rigid confocal fluorescence microscopes [43][44][45] have reported that histological architecture of breast core biopsies and excision specimens, respectively, could be visualized in real time. Whilst these microscopes may have a role for imaging resection margins of excised specimens, in situ imaging of cavity walls during surgery warrants significant miniaturization to enable insertion through a small 3-4 cm skin incision and for deployment against the lateral walls of the breast cavity.…”
Section: Image Interpretation Assessmentmentioning
confidence: 99%
“…In dermatological settings, for example, confocal mosaicking technology is being implemented for the detection of residual basal cell carcinoma margins to guide Mohs surgery of skin. [20][21][22][23] Dobbs et al 7 conducted an initial study to evaluate the usefulness of confocal microscopy for breast specimens. In this study, the mosaics (composite confocal images) were compared to the hematoxylin and eosin (H&E)-stained sections, and single images of ROIs in size 750 × 750 μm 2 were extracted for evaluation by the reader (pathologist).…”
Section: Introductionmentioning
confidence: 99%